Neurorehabilitation in dystonia care: key questions of who benefits, what modalities, and when to intervene - Hikaru Kamo; Hikaru Kamo; Koichi Nagaki; Koichi Nagaki; Alison R. Kraus; Lisa Warren; Aparna Wagle Shukla (Dystonia)
Dystonia causes involuntary, patterned movements and posturing, often leading to disability, pain, and reduced quality-of-life. Despite standard treatments such as botulinum toxin (BoNT) injections, oral medications, and deep brain stimulation therapy, many patients continue to experience persistent symptoms. There is growing evidence supporting the use of rehabilitation-based therapies in the management of certain forms of dystonia. This review summarizes the current body of evidence, which primarily focuses on cervical dystonia (CD) and task-specific dystonia (TSD). The greatest therapeutic potential appears to lie in using these interventions as adjuncts to BoNT therapy. In CD, physical therapy has shown effectiveness when aimed at reducing overactivity in the affected neck muscles through techniques such as stretching, massage, and biofeedback. Concurrently, strengthening the opposing muscle groups helps promote improved posture, reduce pain, and enhance range of motion. In TSD, many studies applied splinting of unaffected body parts (sensory-motor retuning) to encourage adaptive retraining of affected body parts (principles of constraint-induced movement therapy), or alternatively restricting movements of affected body parts to promote sensory reorganization. Although there is high risk of bias, neuroplasticity-based strategies like motor and sensorimotor training appear to be promising for TSD. Use of kinesiotaping, vibrotactile stimulation, TENS, and orthotics can help modify movement patterns, while biofeedback can reinforce and sustain motor control improvements. Emerging evidence for functional dystonia supports the role of multimodal approach, combining PT with cognitive behavioral therapy or mind-body strategies. The focus is movement retraining to shift attention away from abnormal movements and restore confidence in normal movement to improve outcomes. Regardless of dystonia type, individualized therapy plans are essential. Home-based exercises play a critical role in maintaining the gains achieved during supervised sessions, supporting ongoing progress, and preventing regression.